(untitled) (Comprehensive Journal of Science, 2026)
This research focuses on a contemporary jurisprudential issue: the impact of permanent and temporary cosmetics on worship. This is due to their widespread use, particularly among women, and the rulings that arise from their use, which affect the validity of religious practices such as ritual purity (tahara), ablution (wudu), ritual bathing (ghusl), prayer, fasting, and pilgrimage (Hajj). This research attempts to combine the applied jurisprudential aspects with the objectives of Islamic law (maqasid al-shari’ah). It begins by defining cosmetics and their types, distinguishing between permanent cosmetics such as fillers, Botox, and tattoos, and temporary cosmetics such as kohl, henna, and other easily removable preparations. The research then addresses the ruling on the use of each type based on its effect on ritual purity, relying on relevant Islamic legal evidence and scholarly opinions, and examining its impact on worship and the resulting legal rulings. The research concludes that the objectives of Islamic law regarding adornment revolve around preserving human dignity, maintaining natural beauty, and achieving permissible beauty without transgressing its boundaries.